Hiding in Montana [large type] - Scott, Laura, 1961- (Rocky Mountain K-9 unit, 2022)
"To save a woman from being kidnapped, Officer Chris Fuller and his K-9 partner, Teddy, have no choice but to let the fugitive they're tracking get away. But when the escaped murderer returns to hunt tour pilot Lexie McDaniels again, Chris knows the attempted kidnapping wasn't a chance encounter. Lexie won't be safe until he catches the criminal... but are her secrets what is endangering them all?"--Back cover.